Comments on the article: Sharova AA. Botulinum toxin type A injection in the middle and lower thirds of the face and neck area for aesthetic purposes. Plastic Surgery and Aesthetic Medicine. 2025;3:108–117. (In Russ.). https://doi.org/10.17116/plast.hirurgia2025031108 (Plastic Surgery and Aesthetic Medicine, 2025)
Comments on the article: Sharova AA. Botulinum toxin type A injection in the middle and lower thirds of the face and neck area for aesthetic purposes. Plastic Surgery and Aesthetic Medicine. 2025;3:108–117. (In Russ.). https://doi.org/10.17116/plast.hirurgia2025031108.